Answer:
<h3>x = (y-5)/3</h3>
=========================================
Explanation:
We start with x and multiply it with 3 to get 3x. Then we add on 5 to get 3x+5. This specific order is going to be followed in reverse to undo everything so we can isolate x.
We'll subtract 5 from both sides to undo the "plus 5" operation. Then we'll divide both sides by 3 to undo the "multiply by 3" operation.
---------
This is what the steps look like
y = 3x+5
y-5 = 3x+5-5 ... subtract 5 from both sides
y-5 = 3x
3x = y-5
3x/3 = (y-5)/3 ... divide both sides by 3
x = (y-5)/3